Witnesses of two accidents urged to come forward - New Sarawak, Tribune (New Sarawak Tribune, 2013)
JITRA: Kubang Pasu police yesterday urged anyone who witnessed two accidents at Km22.5 on Wednesday and Km23.1 of the North South Expressway (heading to Changlung) on 4 Dec to come forward and assist the police with information.In the incident on Wednesday, Mohd Malik Samsudin, 30, a worker at a food stall in Universiti Utara Malaysia (UUM), was found dead atKm22.5 of the North South Expressway, near the Gano Excel factory, by passersby at 7.45am.